Petri nets with exclusive entities for decision making. (2013) - Latorre*, J.I.; Jiménez, E.
Abstract: The design of Discrete Event Systems (DES) can be seen as a sequence of decisions leading to a final product that complies with a set of specifications and operates with efficiency. These decisions usually include the choice among a set of alternative structural configurations for the DES. This paper discusses the formalisation of a decision problem based on a DES into an optimisation problem, stressing and making explicit the exclusiveness between alternative structural configurations. This approach broadens and improves the classical methodology for solving the mentioned problems with new ideas and techniques. A significant advantage achieved consists of increasing the efficiency of the solving techniques by removing redundant information in the Petri net model of the DES and by unifying the solution space.